The Making of Oyster Mushroom Log Waste Compost: Study on Goat Manure, EM4 Concentration and Reversal Time - Rahmah, Nur Lailatul; Anggraeni, Sakunda; Pulungan, Maimunah Hindun; Hidayat, Nur; Wignyanto, Wignyanto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
This study aims to determine the effect of goat manure, EM 4, and a reversal of the quality of oyster mushroom log waste compost generated. The experimental design of this study is a randomized block design (RBD) with three factors: the concentration of goat manure (0, 20, and 40%), the concentration of EM4 (0; 0.1 and 0.2%) and time reversal (3, 2, and 1 week) with fermentation time 1 month. Expectations of this study was produced compost that meets the quality standards of organic fertilizers based on SNI 19-7030-2004 ie C / N ratio of 10-20 and pH from 6.8 to 7.49. The results showed that the oyster mushroom logs waste can be composted after one month of composting, where the influence of the concentration of goat manure, EM4 and time reversal significantly affect the C / N ratio, but no significant effect on pH, water content and temperature of the compost. The best treatment is to use goat manure to 40%, 0.1% and EM4 reversal period every 2 weeks. Compost has the best treatment C / N ratio, 14.50; temperature of 29oC; moisture content of 62.24%; pH 7.5; blackish brown color; smooth texture and a slight smell of soil.Keywords: oyster mushroom logs waste, compost, goat manure, EM4, time reversal